1992
DOI: 10.1002/jctb.280540302
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of branched alkylbenzene sulphonates

Abstract: Branched alkylbenzene sulphonates (ABS) widely used surfactants in the 1950s and early 1960s were subsequently replaced by linear forms in response to evidence that the former are recalcitrant. Though banned in most countries, the use of branched ABS is still widespread in developing countries. In addition to being recalcitrant, they are xenobiotic and, in nature, the biodegradation process of these surfactants requires a lengthy period. This review elaborates the available information on the biodegradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…While LASs compounds were found to be biodegradable enough (Takada and Ishiwatari 1990;Hashim et al 1992), aromatic sulfonates without long alkyl side chains proved to be biorecalcitrant (Cain 1981). Benzene-and naphthalenesulfonates with sulfo, nitro and amino groups are characterized by especially low biodegradability (Brilon et al 1981;Zürrer et al 1987;Wittich et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…While LASs compounds were found to be biodegradable enough (Takada and Ishiwatari 1990;Hashim et al 1992), aromatic sulfonates without long alkyl side chains proved to be biorecalcitrant (Cain 1981). Benzene-and naphthalenesulfonates with sulfo, nitro and amino groups are characterized by especially low biodegradability (Brilon et al 1981;Zürrer et al 1987;Wittich et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can be partly attributed to the hindered formation of HO  radicals from 243 ozone because in these reactions ozonide ions are in protonated form (see reactions (5)(6)(7)(8)). 244…”
Section: About Here 242mentioning
confidence: 99%
“…Due to the resemblance of AS to fatty acids, yeast may metabolize AS via the fatty acid β-oxidation pathway in the peroxisome. Indeed, others (23,24) have reported that metabolism of n-alkyl sulfates-based surfactants such as LAS (linear alkyl benzene sulfonates) begins via oxidation of the terminal methyl group of the alkyl chain (ω-and β oxidation) (25).…”
Section: Fatty Acid β-Oxidation Pathway Is Involved In As Assimilationmentioning
confidence: 99%